1997
DOI: 10.1159/000283054
|View full text |Cite
|
Sign up to set email alerts
|

Is Renal Function at the Tumor Side a Prognostic Factor in Ureteral Transitional Cell Carcinoma?

Abstract: Objectives: To evaluate whether the ipsilateral renal function on the tumor side is a prognostic factor in transitional cell carcinoma (TCC) of the ureter. Patients and Methods: We retrospectively reviewed 129 consecutive patients with ureteral TCC between September 1973 and July 1993 at our hospital. There were 98 males and 31 females aged from 31 to 84 years (mean 64.9). Of them, 126 patients who received intravenous pyelography (IVP) were divided into 3 groups according to their radiological findings (group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 6 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…In addition, hydronephrosis also correlated with the T stage. 21,22 Presently, hydronephrosis and T stage did not correlate. Therefore, we investigated whether the anatomical location of urothelial carcinoma (renal pelvis vs. ureter) and degree of hydronephrosis has real prognostic value for UUTUC.…”
Section: Cuaj • April 2013 • Volume 7 Issues 3-4 E218mentioning
confidence: 76%
“…In addition, hydronephrosis also correlated with the T stage. 21,22 Presently, hydronephrosis and T stage did not correlate. Therefore, we investigated whether the anatomical location of urothelial carcinoma (renal pelvis vs. ureter) and degree of hydronephrosis has real prognostic value for UUTUC.…”
Section: Cuaj • April 2013 • Volume 7 Issues 3-4 E218mentioning
confidence: 76%
“…As a result, UTUC might progress during the development of hydronephrosis (13). Second, several studies reported that patients with hydronephrosis had a more advanced tumor stage than those without hydronephrosis (13,14,28). In addition, ureteral tumors were reported to be more likely to present with hydronephrosis and to have a worse prognosis than renal pelvic tumors, which could be attributed to the thin layer of surrounding ureteral adventitia containing an extensive plexus of blood vessels and lymphatic channels, making tumor invasion and metastasis easier (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…13,14 In addition, delayed ipsilateral renal excretion in patients with ureteral tumors has been associated with decreased survival on univariate analysis. 15 We sought to confirm this relationship with our own, single-institutional UTUC population. Realizing that UTUC may have a different prognosis dependent on tumor location, we also sought to determine if the location of the primary tumor (renal pelvis/ calices vs ureter) changed this association.…”
mentioning
confidence: 93%